CASH HOLDING PERUSAHAAN SEKTOR OTOMOTIF - Salsabilah, Nadia; Lautania, Maya Febrianty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This research investigates the relationships between growth opportunity, net working capital, and cash conversion cycle with cash holdings of publicly listed automotive companies on the Indonesian stock exchange during the live years (2017-2021). The data used in this research was obtained from 14 publicly listed automotive companies, and collected through saturation sampling. This research employs a panel data regression model due to the data in this research sharing the characteristic of the data panel where the Fixed Effect Model (FEM) is assumed to be an appropriate model because the value of intercept in this research is individually different. Using Eviews 12, the first step is to assess whether the data follows a normal distribution and to evaluate the suitability of the FEM for this research. Finally, the estimation process is conducted to present the result of this research. This research shows that growth opportunities, net working capital, and cash conversion cycles simultaneously affect cash holding with an 80.17% confidence in explaining variations in cash holdings. However in partial, growth opportunity and cash conversion cycle do not affect cash holding, while net working capital negatively influences cash holding.